"VOICE MAP", APLIKASI PENUNJUK ARAH UNTUK MEMBANTU PENYANDANG TUNA NETRA MEMANFAATKAN TEKNOLOGI VOICE RECOGNITION BERBASIS SMARTPHONE - Putra, Bayu Aji Mahendra; Maulana, Ekky Arya Sukarno (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Starting from the high level of the blind people in Indonesia, need for various kinds of technologies that can help them doing activities. One of the points that can be technology development is do improve their ability to use other senses than the sense of sight. Developing a technology that can replace humans will be very useful for blind persons to reduce their dependence on others. Technological developments are starting to break into parts capable of mimicking human nature can be developed to help the problems of society, especially the problems experienced by blind persons where most still require another person to assist in daily activities, such as traveling. Through literature studies that have been done, voice recognition and site search is emerging technology and can be used to facilitate the blind persons to find a place, so that both the technology chosen for combined in a "V-Map" application. In designing and building software systems, "V-Map" which is able to produce technology which helps the user in providing direction using voice and receive voice as an orders. The development of smartphones is very precise to be a support tools of this technology because it can be taken anywhere besides voice recognition in smartphones also continued to progress, so that the "V-Map" can be created by using the smartphone as a supporting tool. "V-Map" can be accessed through voice and can provide sound direction and provide a new solution for a variety of map developers because it provides a breakthrough in the form of the address stored in the contact. Contacts are accessible through voice then "V-Map" to access the contact location and issue commands to the users to approach the address.Keywords : Blind people, Technology, voice recognition, site search, smartphone.